O processo interpretativo na regência orquestral: um estudo a partir da obra Appalachian Spring – Ballet for Martha (suite for 13 instruments) de Aaron Copland - Teixeira, Fellipe Rafael Carnaúba (2017)
The present research aims to report in detail the interpretive process of the conductor, from the perspective of the author of this work, using the work Appalachian Spring (1944) by the American composer Aaron Copland (1900 - 1990). The motivating question of this research is about how the interpretative process of conductor takes place, since it does not have the apparatus of the orchestra at the moment of preparation of the work. The first chapter, the introduction, presents a general study of the musical interpretation, the objectives, the justification and the methodology. In the second chapter, development of the research, there are three points of study: one on the construction of orchestral sonority on the part of the conductor, as it happens, the steps, difficulties and importance of this process for the musical accomplishment; a study on the musical silences and the importance of their observation for the work interpretation; and finally the analysis of the gestural repertoire used by the conductor in the work in question. Still in the development, the work brings the report of experience of the author on how he gave his rehearsals and his perspective until the concert. In the third chapter there is the conclusion of the research. In the annexes will be present the score with the markings of study of the author of the work